Why Politics and Context Matter in Conservation Policy. Issue 2 (13th March 2017) - Damiens, Florence L. P.; Mumaw, Laura; Backstrom, Anna; Bekessy, Sarah A.; Coffey, Brian; Faulkner, Richard; Garrard, Georgia E.; Hardy, Mathew J.; Kusmanoff, Alexander M.; Mata, Luis; Rickards, Lauren; Selinske, Matthew J.; et al.
Abstract: Kareiva and Fuller (2016) consider the future prospects for biodiversity conservation in the face of the profound disruptions of the Anthropocene. They argue that more flexible and entrepreneurial approaches to conservation are needed. While some of the approaches they promote may work in particular situations, we believe their proposal risks unintended and detrimental social and ecological consequences by presenting them as global solutions to complex political, economic, social and ethical problems that are context‐dependent. Here we argue that the authors inadequately considers the following core issues of biodiversity conservation, namely: (1) the structural causes of biodiversity depletion and the responsibilities of key actors; (2) the questions around what should be conserved, the processes by which biodiversity is valued, and who has the legitimate authority to value it; (3) the fact that new tools, technologies and innovative approaches are unsuitable as guiding principles to solve complex, context‐dependent social‐ecological problems; (4) the challenges of choosing relevant interventions, given experts' limited ability to 'manage for change and evolution'; and (5) the risks associated with promoting a utilitarian approach and a neoliberal governance model for conservation at the global scale. Abstract : In general, tools and technologies, whether commonly used or innovative, should not be presented as guiding principles for solving complex social‐ecological problems. Their suitability should be assessed on a case‐by‐case basis, and encompass philosophical and ethical implications, as well as matters of feasibility and holistic impacts.